Cover Feature: Transition‐Metal‐Free and Site‐Selective Selenylation of Heterocyclic N‐Oxides in Anisole as a Green Solvent (Eur. J. Org. Chem. 31/2020). Issue 31 (17th August 2020) - Lee, Suk Hun; Kwon, Na Yeon; Lee, Ji Yoon; An, Won; Jung, Young Hoon; Mishra, Neeraj Kumar; Ghosh, Prithwish; Park, Jung Su; Kim, In Su
Abstract : The Cover Feature shows a synthetic protocol for the formation of C2‐selenylated heterocyclic N‐oxide products from heterocyclic N ‐oxides and diaryl selenides in anisole as a green solvent. The synthetic transformations demonstrate the utility of the developed methodology. More information can be found in the Full Paper by P. Ghosh, J. S. Park, I. S. Kim et al.